1997
DOI: 10.1007/bf02305558
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of CD3+CD56+ lymphocytes correlates with induction of cytotoxicity by interleukin-2 gene transfer in human breast tumor cultures

Abstract: IL-2 gene expression by human breast cancer causes expansion of CD3+CD56+ cytotoxic-lymphocytes. This phenotype is consistent with that of a non-major histocompatibility complex (MHC)-restricted cytokine induced killer cell population previously described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Also, persons with a lower CD4/CD8 ratio were found to have higher numbers of these CD3+CD56+lymphocytes in their blood. These natural killer-like T-lymphocytes play an important role in the immunologic reaction against tumours (Lee et al 1996, Schmidt-Wolf et al 1997, Euhus et al 1997). CD3+CD56+lymphocytes were found in elevated numbers in the peripheral blood of patients suffering from ovarian cancer (Schroder et al 1997) or from colorectal cancer (Takii et al 1994) and in at least a subset of patients with monoclonal gammopathies (Famularo et al 1992).…”
mentioning
confidence: 99%
“…Also, persons with a lower CD4/CD8 ratio were found to have higher numbers of these CD3+CD56+lymphocytes in their blood. These natural killer-like T-lymphocytes play an important role in the immunologic reaction against tumours (Lee et al 1996, Schmidt-Wolf et al 1997, Euhus et al 1997). CD3+CD56+lymphocytes were found in elevated numbers in the peripheral blood of patients suffering from ovarian cancer (Schroder et al 1997) or from colorectal cancer (Takii et al 1994) and in at least a subset of patients with monoclonal gammopathies (Famularo et al 1992).…”
mentioning
confidence: 99%
“…Other studies have also reported that NKT-cell proliferation is IL2-dependent [ 108 , 109 ]. For example, breast cancer cells expressing IL2 were shown to cause the expansion of NKT-cells in vitro [ 108 ]. Furthermore, IL2-secreting fibroblasts were shown to increase the NKT-cell counts in patients with peripheral neuroectodermal tumor and, subsequently tumor cell death [ 109 ].…”
Section: Discussionmentioning
confidence: 98%
“…NKT-cells are cytotoxic against tumors, where killing capacity is independent of the T-cell receptor activation [47]. Other studies have also reported that NKT-cell proliferation is IL2-dependent [108,109]. For example, breast cancer cells expressing IL2 were shown to cause the expansion of NKT-cells in vitro [108].…”
Section: Discussionmentioning
confidence: 99%
“…This cytokine also enhances the cytotoxic effect of γδ T-cells, increasing CD69 and degranulation marker CD107a expression and IFNγ secretion (Ribot et al, 2014). Furthermore, IL2 can also promote the expansion of NKT-cells in cancer patients (Euhus et al, 1997;Engel et al, 1998). IL2-based therapy has several significant drawbacks, particularly the stimulation of Tregs, which are associated with the suppression of the antitumor immune response (Boyman et al, 2006).…”
Section: Interleukinmentioning
confidence: 99%